Simulation of energy states in solid solutions based on the ferroelectrics- semiconductors of Sn₂P₂S₆ type - Mitin, O.B.; Kharkhalis, L.Yu.; Mikajlo, O.A.; Melnichenko, T.N.; Dorogany, V. (Condensed Matter Physics, 2000)
The energy spectra of charge carriers in several models of the ordered solid
solutions and virtual crystal model based on the ferroelectrics of Sn₂P₂S₆
type are calculated by the semiempirical pseudopotential method. It is
shown that the band gap depends on the employed model of the solid
solution. Методом напівемпіричного псевдопотенціалу розраховані енергетичні спектри носіїв заряду в деяких моделях впорядкованих твердих
розчинів і моделі віртуального кристала на основі сегнетоелектриків-напівпровідників типу Sn₂P₂S₆. Показано, що ширина забороненого
зони суттєво залежить від вибраної моделі твердого розчину.